2020
DOI: 10.1177/1120700020978587
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of collapse in femoral head osteonecrosis: role of volumetric assessment

Abstract: Purpose: The purpose of this study was to evaluate and compare the accuracy of three different techniques of measuring the extent of osteonecrosis involvement of the femoral head on MRI to determine the best predictor of collapse and to identify the size of the lesion volume which best predicts collapse. Methods: We prospectively enrolled 48 hips of osteonecrosis femoral head (ONFH) with stage 1 or 2 osteonecrosis and the enrolled patients were followed up for 1 year. Angular measurements (modified Kerboul Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Manual calculation in all MRI sections, a cumbersome task, has also been criticised due to the potential inter- and intraobserver variability in determining the reference FHV. 31 - 33 We performed both manual (based on the anatomical contour) and automatic (based on a spherical model) calculations of the femoral head, as mentioned in Supplementary Figure b. Data shown in the results are obtained as a percentage of the manual measured FHV.…”
Section: Discussionmentioning
confidence: 99%
“…Manual calculation in all MRI sections, a cumbersome task, has also been criticised due to the potential inter- and intraobserver variability in determining the reference FHV. 31 - 33 We performed both manual (based on the anatomical contour) and automatic (based on a spherical model) calculations of the femoral head, as mentioned in Supplementary Figure b. Data shown in the results are obtained as a percentage of the manual measured FHV.…”
Section: Discussionmentioning
confidence: 99%
“…Ansari et al 42 . drew the necrotic area in outline in coronal planes of MRI, calculated the necrotic lesion/the entire femoral head area ratio in each slice, and finally determined the sum of the area ratio multiplied by the slice thickness to obtain the volumetric measurement.…”
Section: Structural Deterioration In Necrotic Femoral Headmentioning
confidence: 99%
“…Ansari et al . 42 drew the necrotic area in outline in coronal planes of MRI, calculated the necrotic lesion/the entire femoral head area ratio in each slice, and finally determined the sum of the area ratio multiplied by the slice thickness to obtain the volumetric measurement. Their results showed that 90.6% of hips collapsed within 1 year in lesion volume greater than 25% of femoral head, while 31.3% of hips collapsed in lesion volume less than 25%.…”
Section: Structural Deterioration In Necrotic Femoral Headmentioning
confidence: 99%
“…Partial-volume artifacts are minimized on sub 1.0-mm 3D acquisitions. Accurate assessment of lesion size, 61 its location, presence of joint synovitis, and early osseocartilaginous collapse, are important for surgical decision making. High-resolution 3D MRI is able to demonstrate such fine details (►Fig.…”
Section: Other Conditions Avascular Necrosismentioning
confidence: 99%